MANAGEMENT EVALUATION OF AN INCLUSIVE EDUCATION PROGRAM IN AN ELEMENTARY SCHOOL: A CIPP MODEL CASE STUDY - Oki Dermawan; Imah Salamah; Shuaibu Umar Gokaru (PEDAGOGIK : JURNAL PENDIDIKAN, 2025)
Inclusive education in Indonesia continues to face implementation gaps, especially in teacher capacity, accessibility, and stakeholder participation. This study evaluated the management of an inclusive education program in an anonymized elementary school in Metro City, Lampung Province, using the Context–Input–Process–Product (CIPP) model. A qualitative evaluative case study was conducted over approximately four weeks, drawing on classroom and school observations (around six sessions across three grade levels), semi-structured interviews with key stakeholders (n≈12), and document analysis (planning, budgeting, curriculum, supervision, and student learning records). Contextual conditions were supportive, reflected in community demand for non-discriminatory access, policy alignment, and a peer-supportive school culture. Inputs were partly adequate: teachers showed strong commitment and used the flexibility of the Merdeka Curriculum, but technical capacity for adaptive assessment and individualized planning varied, while accessibility features and specialized learning supports remained limited. Implementation was generally consistent through differentiated, child-friendly instruction, peer-support routines, and reflective supervision, although time constraints and uneven family engagement reduced the consistency of individualized support. Outcomes were most evident in socio-emotional development and participation; academic progress was reported but not consistently documented across classes. Strengthening routine individualized planning and progress monitoring, focused technical development for teachers, and more stable resourcing and partnerships are needed to sustain improvements.